2021
DOI: 10.3389/fpsyg.2021.616426
|View full text |Cite
|
Sign up to set email alerts
|

Autogenic Training Improves the Subjective Perception of Physical and Psychological Health and of Interpersonal Relational Abilities: An Electronic Field Survey During the COVID-19 Crisis in Spain

Abstract: Currently, humanity is facing one of the most critical situations of this century, the COVID-19. The adverse effects of the pandemic on the mental health of the population are well known. Fear of illness, confinement, lack of financial resources, or poor social support can influence people’s mental state. Despite these risks, several psychological resources may help address this situation. The present study investigated the effectiveness of a self-relaxation techniques known as autogenic training. Autogenic tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Adequate implementation of techniques that eliminate the high level of the cognitive component of the variable can, according to our assumptions, help athletes increase their performance in a given type of sport [ [1] , [2] , [3] , [4] , [5] , 88 ]. This is also in line with research dealing with increasing psychological readiness using yoga exercises [ 66 ], meditations [ [67] , [68] , [69] , [70] ], or using Schultz's autogenic training or Jacobson's progressive relaxation [ [71] , [72] , [73] , [74] , [75] ].…”
Section: Discussionsupporting
confidence: 84%
“…Adequate implementation of techniques that eliminate the high level of the cognitive component of the variable can, according to our assumptions, help athletes increase their performance in a given type of sport [ [1] , [2] , [3] , [4] , [5] , 88 ]. This is also in line with research dealing with increasing psychological readiness using yoga exercises [ 66 ], meditations [ [67] , [68] , [69] , [70] ], or using Schultz's autogenic training or Jacobson's progressive relaxation [ [71] , [72] , [73] , [74] , [75] ].…”
Section: Discussionsupporting
confidence: 84%
“…Because the COVID-19 pandemic has not yet ended, the government, universities, and families need to pay close attention to the physical and mental health of undergraduate students. Interpersonal issues, as well as mental symptoms, require appropriate interventions, which may minimize the unavoidable psychological impact of the pandemic ( 31 ). It is necessary to carry out health education and provide undergraduate students with relevant information on mental health, physical health, academic skills, fitness and other factors that will improve their lives in a timely manner.…”
Section: Discussionmentioning
confidence: 99%
“…Personality characteristics such as suspiciousness, sensitivity and timidity affect an individual's cognitive evaluation of things ( 16 , 17 ). Personality can create unrealistic psychological conflicts, setbacks and other psychological stimuli, preventing people from choosing effective coping methods to eliminate the psychological stress response ( 31 – 33 ). It is mentioned in the social cognitive theory that mental health problems caused by stress are more likely to occur in people who choose to escape psychologically and regard the stressors as a long-term catastrophic threat.…”
Section: The Impacts On the Mental Health Of Undergraduate Students C...mentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies showed the effectiveness of AT in reducing anxiety and stress disorders [ 37 , 83 ]. A recent study [ 84 ] focused on how AT could help youth to cope with the pandemic; it reported strong beneficial effects of this practice on adolescents’ physical, psychological and relational health, recommending the practice of AT to people who experience anxiety, are afraid of illness, or feel that they have to improve the quality of their relationships with others.…”
Section: Discussionmentioning
confidence: 99%